Two grass pollen tablets commercially available for allergy immunotherapy display different IgE epitope repertoires. Issue 1 (27th February 2019) - Batard, Thierry; Sanjuan, Amparo; Denis, Laure; Nguyen, Hélène; Montagut, Armelle; Sastre, Joaquín; Rak, Sabina; Cuiné, Jean F.
Abstract: Background: The distribution of Pooideae species varies across Europe. Especially, Timothy is less represented in Southern than in Northern Europe. Since allergenic cross‐reactivity between pollens from different grasses is only partial, grass pollen‐allergic patients are expected to display different sensitization profiles, with specific IgE directed against different combinations of allergenic epitopes, depending on their living places in Europe and the grasses they are exposed to. In this context, this study aimed at comparing two tablets commercially available for allergy immunotherapy, namely a 5‐grass (Cocksfoot, Meadow‐grass, Rye‐grass, Sweet vernal‐grass and Timothy) and a 1‐grass (Timothy) pollen tablets, for their ability to represent the sensitization profiles of patients, depending on whether they live in Southern or Northern Europe. Methods: Sera were collected from adult patients living in Spain (n = 19) and Sweden (n = 22). Tablets were compared for their ability to inhibit the binding of patient serum IgE to pollen allergens from twelve grasses commonly distributed throughout Europe, as determined by the areas under the curves obtained by ELISA‐inhibition. Tablets were adjusted to an equivalent allergenic activity, based on the CBER/FDA bioequivalent allergy unit. Results: Inhibition of the IgE binding to pollen allergens from twelve grasses was significantly stronger with the 5‐grass than with the 1‐grass pollen tablet ( p  < 0.0001), regardless of whether patients were considered as a whole or by geographical area. This difference between tablets was significantly greater for Southern than Northern European patients ( p  < 0.05). Conclusions: Compared to the 1‐grass tablet, the 5‐grass tablet generally covers better the sensitization profiles of European patients, especially patients from Southern Europe, in principle less exposed to pollen from Timothy than from other grasses. The 5‐grass tablet is therefore expected to elicit larger spectra of blocking antibodies, which might have implications in light of the generally accepted mechanisms of allergy immunotherapy.